Pemberdayaan Perempuan Terhadap Penenun Sarung Sutra Mandar Di Desa Tammejarra Kecamatan Balanipa Kabupaten Polewali Mandar - Aynun Nyswa; Misbahuddin; St. Aisyah BM; Irwanti Said (Jurnal Berita Sosial, 2025)
The main issue in this research is to examine the form of women's empowerment for silk sarong weavers in Tammejarra Village and to identify the supporting and inhibiting factors in the empowerment process. The research questions raised in this study are: (1) What is the form of empowerment for women silk sarong weavers? and (2) What are the supporting and inhibiting factors of the empowerment process?. This study uses a qualitative descriptive research method, located in Tammejarra Village, Balanipa Subdistrict, Polewali Mandar Regency, and employs a sociological approach. The data sources consist of both primary and secondary data. Data collection techniques include observation, interviews, and documentation with silk sarong weavers, community leaders, and relevant institutions. Data analysis was carried out through three stages: data reduction, data display, and conclusion drawing. The results of this study are: (1) Skills enhancement, through weaving training and the introduction of traditional Mandar motifs; (2) Economic empowerment, through the provision of tools and materials, the formation of joint business groups, and access to marketing; and (3) Social empowerment, which includes strengthening solidarity, participation in village deliberations, and the preservation of Mandar cultural identity. The supporting factors include: a) The inheritance of weaving skills passed down through generations; b) Support from the village government and relevant agencies; and c) The high cultural value attached to Mandar silk sarongs. The challenges faced include: a) Limited availability of raw materials; b) Lack of advanced training; c) Limited access to modern markets; and d) Low interest among the younger generation in continuing the weaving tradition. Tanya ChatGPT. The implication of this research is that traditional craft-based women’s empowerment can be an effective strategy to improve family welfare while preserving local cultural heritage. Therefore, continuous collaboration between the government, community, and private sector is needed to promote inclusive, sustainable, and community-based empowerment.